2018
DOI: 10.1016/j.aucc.2017.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Nurse titrated analgesia and sedation in intensive care increases the frequency of comfort assessment and reduces midazolam use in paediatric patients following cardiac surgery

Abstract: Introducing a pain and sedation protocol changed bedside nurse practice in pain and sedation management. The protocol has enabled nurses to provide pain and sedation management in a consistent and timely manner and reduced the dose of midazolam required to maintain comfort according to the patients COMFORT B scores. Individual evaluation of practice change is recommended to units who implement nurse led analgesic and sedative protocols to monitor changes in practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(51 citation statements)
references
References 43 publications
0
45
0
6
Order By: Relevance
“…It is possible that the implemented protocols directed clinicians away from midazolam use and hence is an expected result. The studies also showed that using less midazolam in the PICU was not harmful and resulted in higher success in meeting sedation targets (31) without an increase in adverse effects. Literature to support minimization of benzodiazepines is useful, as growing evidence suggests that benzodiazepines can have a negative impact on cognitive development and incidence of delirium (8,10).…”
Section: Are We Asking the Right Questions About Sedation Protocols?mentioning
confidence: 90%
See 3 more Smart Citations
“…It is possible that the implemented protocols directed clinicians away from midazolam use and hence is an expected result. The studies also showed that using less midazolam in the PICU was not harmful and resulted in higher success in meeting sedation targets (31) without an increase in adverse effects. Literature to support minimization of benzodiazepines is useful, as growing evidence suggests that benzodiazepines can have a negative impact on cognitive development and incidence of delirium (8,10).…”
Section: Are We Asking the Right Questions About Sedation Protocols?mentioning
confidence: 90%
“…Most studies, including the large RESTORE study (25), have shown no difference in these outcome measures (25,(27)(28)(29). The exceptions were one Korean study, which showed a decrease in duration of MV (21), and an Australian study, which demonstrated an increase in duration of MV (31). In the latter study, the authors reported a significant number of younger children in the post-implementation phase who were less likely to be extubated early post-cardiac surgery.…”
Section: What Is the Evidence For A Sedation Protocol?mentioning
confidence: 99%
See 2 more Smart Citations
“…7 Optimising care protocols to provide correct pain control and an optimal degree of sedation at intensive care unit (ICU) admission reduces the anxiety of children and has a positive impact on reducing the pain, distress, and discomfort of these patients. 8,9 The most commonly used strategy for managing the comfort of critically ill paediatric patients is sedation and analgesia. 3,10,11 The optimal use of analgosedation allows for invasive procedures to be carried out safely by permitting synchronisation and patient tolerance of mechanical ventilation (MV), 11 preventing accidental extubation and reducing both metabolic 12 and oxygen consumption in the case of shock.…”
Section: Introductionmentioning
confidence: 99%